HUBUNGAN AKTIVITAS FISIK DENGAN KESEHATAN MENTAL SISWA DI ERA DIGITAL SMAN 2 LABUAPI - Lalu Rensa Haqqulyaqin Islam; Sri Erny Muliyani; Sukarman (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study aimed to analyze the relationship between physical activity and students’ mental health in the digital era at SMAN 2 Labuapi. The study employed a quantitative approach with a correlational design. The population consisted of 552 students, and 59 students were selected as the sample using purposive sampling. Physical activity was measured using the Physical Activity Questionnaire for Adolescents (PAQ-A), while mental health was assessed using the Self Reporting Questionnaire-20 (SRQ-20). Data were analyzed descriptively and bivariately using the Chi-Square test. The findings showed that most students were in the moderate physical activity category (62.7%), while 55.9% were classified as having good mental health or no indication of emotional mental disorders. The Chi-Square test revealed a significant relationship between physical activity and mental health (χ² = 7.589; p = 0.022). Students with higher levels of physical activity tended to have better mental health conditions. These findings indicate that physical activity is an important protective factor for students’ psychological well-being in the digital era.